2021
DOI: 10.3390/nu13072471
|View full text |Cite
|
Sign up to set email alerts
|

Use of Different Food Classification Systems to Assess the Association between Ultra-Processed Food Consumption and Cardiometabolic Health in an Elderly Population with Metabolic Syndrome (PREDIMED-Plus Cohort)

Abstract: The association between ultra-processed food (UPF) and risk of cardiometabolic disorders is an ongoing concern. Different food processing-based classification systems have originated discrepancies in the conclusions among studies. To test whether the association between UPF consumption and cardiometabolic markers changes with the classification system, we used baseline data from 5636 participants (48.5% female and 51.5% male, mean age 65.1 ± 4.9) of the PREDIMED-Plus (“PREvention with MEDiterranean DIet”) tria… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 78 publications
1
55
0
2
Order By: Relevance
“…Post hoc exploratory analyses further suggested several interactions by sex in regression models predicting dietary pattern adherence; however, there was insufficient statistical power to conduct stratified analyses by sex in this study. Additionally, in contrast to many Westernized countries, this cohort does not consume large quantities of processed hyperpalatable foods [ 42 ], which may have influenced their taste perception profiles and food choices. To fully understand the impact of taste perception profiles on diet quality will require the replication of this analysis in multiple, diverse cohorts and in various food environments.…”
Section: Discussionmentioning
confidence: 99%
“…Post hoc exploratory analyses further suggested several interactions by sex in regression models predicting dietary pattern adherence; however, there was insufficient statistical power to conduct stratified analyses by sex in this study. Additionally, in contrast to many Westernized countries, this cohort does not consume large quantities of processed hyperpalatable foods [ 42 ], which may have influenced their taste perception profiles and food choices. To fully understand the impact of taste perception profiles on diet quality will require the replication of this analysis in multiple, diverse cohorts and in various food environments.…”
Section: Discussionmentioning
confidence: 99%
“…This, together with the evidence showing their negative impact on health [ 9 , 10 , 14 18 ], has turned UPF consumption into a potential public health concern [ 19 ] in need of more solid research. While the term UPF is mainly attributed to the NOVA system, other food processing-based classification systems have described foods and drinks of similar characteristics under their categories of HPF [ 20 , 21 ], so we will use the term HPF to refer to this type of foods.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous studies have demonstrated a link between the risk of developing non-communicable diseases and HPF consumption [ 12 , 17 , 22 27 ], epidemiological research faces some hurdles in this field. First, the existence of multiple food processing-based classification systems based on different criteria [ 21 , 28 ] results in heterogeneous conclusions regarding health outcomes depending on the system used, as shown recently for cardiometabolic health markers [ 20 ]. Second, the lack of an effective tool to assess HPF consumption in clinical studies severely hinders the downstream analysis of its relationship to disease risk.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations